PENGARUH ABDOMINAL STRETCHING EXERCISE TERHADAP INTENSITAS NYERI DISMENOREA - Weny Windastiwi; Wahyu Pujiastuti; Mundarti Mundarti (JURNAL KEBIDANAN, 2017)
The prevalence of dysmenorrhoea is quite high in the world, where an estimated 50% of all women in the world suffer from dysmenorrhea in a menstrual cycle (Calis, 2011). Menstrual disorders require special attention because if not handled can affect the quality of life and activities of daily living (Iacovides, 2013). The purpose of this research was to determine the effect of abdominal stretching exercise on pain intensity dysmenorrhoea. This study was conducted in Junior High School 1 Wonoboyo Temanggung. The method used quasi-experimental research design is one group pretest posttest. The population in this study were all students of Junior High School N 1 Wonoboyo the academic year 2015/2016 with a history of dysmenorrhoea in the last 2 months (December and January) as many as 55 students. The sampling technique used simple random sampling with a sample of 48 respondents. The results showed that the intensity of dysmenorrhea pain abdominal stretching before exercise 75% of respondents experienced a moderate dysmenorrhea and there were 8 respondents severe dysmenorrhoea. The intensity of dysmenorrhea pain after abdominal stretching exercise showed that out of 48 respondents, no respondents with severe dysmenorrhea pain and 85% had moderate dysmenorrhea. P value 0.000 and the value of z = 4, 689 means no abdominal stretching exercise influence on the intensity of pain dysmenorrhoea with. From the results of this study are expected Adolescents who experience painful menstruation or dysmenorrhea should do abdominal stretching exercise to reduce the intensity of the pain.